Consumen Expectations about the Model of Vegetable Menu at Restaurants in Padang City in 2020 - Andrafikar; Handayani, Marni; Safyanti (POLTEKKES KEMENKES PADANG, 2023)
Based on the 2014 Total Diet Survey (SDT) data, it shows that the average consumption of vegetables and their processed products for the Indonesian population is 57.1 grams per person per day. Meanwhile, the average vegetable consumption for the population of West Sumatra province is 45.4 grams, including the 5th lowest vegetable consumption nationally and very far from the WHO recommendation of 250 grams/day. This condition is supported by the community environment where most Padang restaurants or restaurants provide very limited types of vegetables. Whereas West Sumatra is known as a center for vegetable production. This study aims to obtain a model of the vegetable menu that consumers want in restaurants in the city of Padang. The population in this study are restaurant consumers in the city of Padang. The sample is calculated using the formula for the estimation of the proportion of one population and is taken by simple random sampling with predetermined criteria. Data on consumer opinions and desires about the vegetable menus available in restaurants were obtained by means of interviews conducted by interviewers who previously had equalized perceptions. The data is processed using a computer through the stages of checking, coding, entering data, and cleaning data. Data analysis was carried out descriptively to describe consumer opinions and desires about the vegetable menu at restaurants in the city of Padang and to describe the desired vegetable menu model. The results showed that 60% of restaurant consumers in the city of Padang stated that the types of vegetables/types of vegetable dishes were less varied, 52.5% did not like the vegetables served, 52.5% small vegetable portions, 77.5% no vegetable dishes. specifically, 70% did not choose a restaurant because they did not like the vegetables served, 85 chose spinach/kale as the vegetables provided, and 90% of consumers stated that the type of vegetable dish they wanted was boiled/clear and stir-fried.